2015
DOI: 10.4236/wjnst.2015.54026
|View full text |Cite
|
Sign up to set email alerts
|

Some Insights into Cluster Structure of <sup>9</sup>Be from <sup>3</sup>He + <sup>9</sup>Be Reaction

Abstract: The study of inelastic scattering and multi-nucleon transfer reactions was performed by bombarding a 9 Be target with a 3 He beam at the incident energy of 30 MeV. Angular distributions for 9 Be(3 He, 3 He) 9 Be, 9 Be(3 He, 4 He) 8 Be, 9 Be(3 He, 7 Be) 5 He, 9 Be(3 He, 6 Li) 6 Li and 9 Be(3 He, 7 Li) 5 Li reaction channels were measured. Experimental angular distributions for the corresponding ground states (g.s.) were analyzed within the framework of the optical model, the coupled-channel approach and the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…It should be noted that a similar result was reported earlier in [18]. One-step transfer of the 5 He cluster was also indicated as a dominant process by Jarczyk et al [33] in studying the 12 C( 11 B, 6 Li) 17 O and 12 C(d, 7 Li) 7 Be reactions.…”
Section: Cluster-transfer Reactionsupporting
confidence: 83%
See 1 more Smart Citation
“…It should be noted that a similar result was reported earlier in [18]. One-step transfer of the 5 He cluster was also indicated as a dominant process by Jarczyk et al [33] in studying the 12 C( 11 B, 6 Li) 17 O and 12 C(d, 7 Li) 7 Be reactions.…”
Section: Cluster-transfer Reactionsupporting
confidence: 83%
“…In our previous works [5][6][7], the 3 He interaction with 9 Be was studied and angular distributions of the reaction products in the following exit channels: 3 He + 9 Be, 5 He + 7 Be, 5 Li + 7 Li, 6 Be + 6 He, and 6 Li + 6 Li, were measured. The obtained data were analysed within the framework of the optical model (OM), the coupled-channel (CC) and the distorted-wave Born approximation (DWBA) approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The cluster model density distribution has been used successfully to analyze elastic scattering cross sections of unstable projectile nuclei (see, e.g., Refs. [23,24,25,26,27,28]. Four different forms of cluster density distributions of the projectile nucleus are considered in this study and each is presented in the following section.…”
Section: Cluster Density Distribution Of 10 C Nucleusmentioning
confidence: 99%
“…Thus, a structure consisting of nucleons can be thought as one body [1]. In this respect, the 9 Be nucleus can be assumed as α + α + n, d + 7 Li, 3 H + 6 Li, 3 He + 6 He and n + 8 Be cluster structures [2][3][4] although the cluster structure of 9 Be is not known exactly yet [5]. Therefore, cluster structure is still a hot topic, and many studies can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%